Discovery of MK‐8970: An Acetal Carbonate Prodrug of Raltegravir with Enhanced Colonic Absorption. Issue 2 (2nd December 2014) - Walji, Abbas M.; Sanchez, Rosa I.; Clas, Sophie‐Dorothee; Nofsinger, Rebecca; de Lera Ruiz, Manuel; Li, Jing; Bennet, Amrithraj; John, Christopher; Bennett, David Jonathan; Sanders, John M.; Di Marco, Christina N.; Kim, Somang Hope; et al.
Abstract Developing new antiretroviral therapies for HIV‐1 infection with potential for less frequent dosing represents an important goal within drug discovery. Herein, we present the discovery of ethyl (1‐((4‐((4‐fluorobenzyl)carbamoyl)‐1‐methyl‐2‐(2‐(5‐methyl‐ 1, 3, 4‐oxadiazole‐2‐carboxamido)propan‐2‐yl)‐6‐oxo‐1, 6‐dihydropyrimidin‐5‐yl)oxy)ethyl) carbonate (MK‐8970), a highly optimized prodrug of raltegravir (Isentress). Raltegravir is a small molecule HIV integrase strand‐transfer inhibitor approved for the treatment of HIV infection with twice‐daily administration. Two classes of prodrugs were designed to have enhanced colonic absorption, and derivatives were evaluated in pharmacokinetic studies, both in vitro and in vivo in different species, ultimately leading to the identification of MK‐8970 as a suitable candidate for development as an HIV therapeutic with the potential to require less frequent administration while maintaining the favorable efficacy, tolerability, and minimal drug–drug interaction profile of raltegravir.